Superconducting Magnetic Energy Storage in Power Grids - Ali, Mohd. Hasan (IET Energy engineering series, 2022)
Energy storage is key to integrating renewable power. Superconducting magnetic energy storage (SMES) systems store power in the magnetic field in a superconducting coil. Once the coil is charged, the current will not stop and the energy can in theory be stored indefinitely. This technology avoids the need for lithium for batteries. The round-trip efficiency can be greater than 95%, but energy is needed for the cooling of the superconducting coil, and the material is expensive. So far, SMES systems are primarily used for improving power quality through short time storage, but further applications are being researched. This concise treatise for researchers, including PhD students, involved with energy storage research at universities and in industry, experts at utilities and grid operators, as well as advanced students provides a hands-on overview of SMES technology. Chapters cover principles, control, power quality and transient stability enhancement, load frequency control, dynamic performance, use of AI with SMES, and cybersecurity case studies underpin the coverage.